Securing the Future through Lifelong Learning: Some Indian Viewpoints - Nair, Geeta (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2024)
This research paper focuses an emerging trend of distance education and online learning witnessed by several nations. The area is covered under Mode I of the General Agreement of Trade in Services (GATS) of the World Trade Organization (WTO) and is fast gaining currency across the globe with major players like the established ones of the West; along with emerging nations like India from the East. It also represents Goal 4 of the Sustainable Development Goals to be attained by 2030. This makes perfect economic sense as it synchronizes all stakeholders’ interests by matching rising demand and aspirations of the youth with not so flexible supply of higher education services in our quest for people-centric and inclusive development. The costs and logistics also create a ‘win-win’ situation for all. Adult education is the greatest beneficiary as ‘second chances’ are created for the ones who the first one; thereby widening people’s choices and opportunities to nurture human resource development. This macro trend is qualitatively enhanced by sharing a micro-level experiment of ‘reaching the unreached’ based on the preliminary findings of my Minor research project. Conference Sub-theme: Social sciences, education, multidisciplinary: Others. Key words: distance education, win-win situation, second chances, Minor research.